The Analysis Of The Effectiveness Of Group Investigation Method Implementation In Increasing Student Learning Outcomes - Mohzana Mohzana; Merla Merla; Yoseb Boari; Muh Adnan Hudain; Ilham Kamaruddin (Mudir : Jurnal Manajemen Pendidikan, 2023)
Through the use of the group investigation approach, this research seeks to improve student learning results. This approach, which is a type of cooperative learning, places an emphasis on the involvement and activity of the students in finding their own learning material (knowledge) that is learned through readily available instructional tools. Classroom action research (CAR) was the research methodology used in this study. To assist teachers in resolving issues that arise in the classroom, classroom action research is conducted. In this study, two cycles with two sessions each were used to perform the research. Interviews, documentation, learning accomplishment exams, and observation logs are the tools that researchers employ. The findings of the research reveal that group investigation-based learning can enhance student learning outcomes, as shown by an improvement in student learning outcomes in cycles I and II. The average value of student learning outcomes was > 75 in cycle I, and it increased to > 80 in cycle II. Along with improving student learning outcomes, the group investigation method can also boost student participation, which will make them more passionate about the learning process.